Review of the genus Gatzara Navás, 1915 from China (Neuroptera: Myrmeleontidae) - Wang, Xinli; Ao, Weiguang; Wang, Zhiliang; Wan, Xia (Zootaxa, 2012)
Six species of the genus Gatzara Navás, 1915 from China are reviewed. One new species Gatzara nigrivena n. sp. is de-scribed and four new combinations, Gatzara angulineura (Yang, 1987), n. comb., Gatzara decorilla (Yang, 1997), n.comb., Gatzara decorosa (Yang, 1988), n. comb., and Gatzara qiongana (Yang, 2002), n. comb., are proposed and thespecies redescribed. Morphological illustrations, a distribution map, and a key to the species of Gatzara from China are provided.